Meningkatkan Hasil Belajar PPKn Menggunakan Model Pembelajaran Examples Non Examples pada Siswa Kelas VIIIE SMP Negeri 6 Salatiga - Mediatati, Nani (Journal of Education Reseach and Evaluation, 2017)
In real conditions of PPkn learning in class VIII E SMPN 6 Salatiga, the teachers only use the lecture method in the delivery of teaching materials and students are passive, so based on the results of the evaluation, there were 19 students (67.85%) have not yet reached Minimum Completeness Criteria ≥76. Based on these problems, its were need to be repaired by Learning model examples of non examples to improve PPKn learning outcomes in class VIII E. Classroom action research is conducted in two cycles and each cycle is carried out through planning, action, observation, and reflection. There were 28 students of class VIII E as the research subject. Methods of data collection are documentation, observation, and test. Technique of data analysis uses quantitative descriptive analysis by comparing the percentage of completeness PPKn learning outcomes before and after the action in cycle 1 and cycle 2. Indicator of research success is learning outcomes corresponding completed PPKn Minimum Completeness Criteria ≥76 achieved to 85% of all students. Result of study shows that increasing outcome of PPKN learning after using examples of non examples learning model. Prior to the act of learning, there were only 9 students (32.15%), which reached Minimum Completeness Criteria ≥ 76, increased to 19 students (67.85%) in cycle 1 and 25 students (89.29%) in the second cycle after the act of learning. Based on the results of this study concluded that using of non examples examples learning model can improve outcomes of PPKn learning in class VIII E SMPN 6 Salatiga.